2016
DOI: 10.1098/rspb.2016.2106
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of natal habitat preference induction within one habitat type

Abstract: Natal habitat preference induction (NHPI) is a mechanism for habitat selection by individuals during natal dispersal. NHPI occurs in wild animal populations, and evidence suggests it may be a common, although little studied, mechanism for post-dispersal habitat selection. Most tests of NHPI examine the influence of distinct, contrasting natal habitat types on post-dispersal habitat selection. We test the hypothesis that NHPI can occur within a single habitat type, an important consideration for habitat special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
(100 reference statements)
2
14
0
Order By: Relevance
“…Variation in the ecological characteristics of the sites may be driving the genetic structure among locations. This finding is consistent with growing evidence that non‐random dispersal resulting from habitat selection, known as “natal habitat preference induction” in rodents, can lead to directed gene flow that promotes phenotypic and genotypic differences between habitat types (Edelaar, Siepielski, & Clobert, ; Mabry & Stamps, ; Merrick & Koprowski, ; Rice, ). For an urban rat, housing, parks and green spaces and mixed‐use infrastructure are very different habitats.…”
Section: Discussionsupporting
confidence: 87%
“…Variation in the ecological characteristics of the sites may be driving the genetic structure among locations. This finding is consistent with growing evidence that non‐random dispersal resulting from habitat selection, known as “natal habitat preference induction” in rodents, can lead to directed gene flow that promotes phenotypic and genotypic differences between habitat types (Edelaar, Siepielski, & Clobert, ; Mabry & Stamps, ; Merrick & Koprowski, ; Rice, ). For an urban rat, housing, parks and green spaces and mixed‐use infrastructure are very different habitats.…”
Section: Discussionsupporting
confidence: 87%
“…NHBD has rarely been reported for wildlife in general [63,64], and has most often been documented in highly heterogeneous habitats ( [9,12], but see [64]). To test for NHBD in Scandinavian wolves, we used different habitat classifications through different clustering methods and number of clusters.…”
Section: Discussionmentioning
confidence: 99%
“…The consistency between parent pack and loner choices regarding proximity to the human habitat corresponds to other studies where habitat preference of dispersing wolves is shown to be determined by early life experiences [ 25 , 26 ]. Such vertical transmission of preferences is thought functional for survival [ 4 , 17 , 18 , 19 , 20 ]. However, this transmission implies that human–wolf conflicts may increase not only because of expanding wolf populations, but also by reproduction of parent packs with the habit to be in proximity of humans and a subsequent dispersal of a new generation that also prefers to be in proximity to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the new generation prefers a habitat comparable to the one in which it was reared. Thus, the vertical transmission of experience enables the new generation to survive efficiently [ 4 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%